OVERACTIVE BLADDER SYNDROME IN CHILDREN - E.L. Vishnevskiy ("Paediatrician" Publishers LLC, 2007)
Overactive bladder is a specific syndrome characterized by bladder dysfunction that is clinically manifested by imperative urination (pollakiuria, urgency, urgent incontinence and nocturia). This state is very widely spread among children: every fifth child aged 4 to 7 shows typical bladder dysfunction. Quite often if urinary distresses are not studied well enough such children are falsely diagnosed with monosymptom enuresis, which, according to our information, actually happens in only 3,9% of cases. When examining children with urinary disorders it is reasonable to be geared to the protocol of European urologist association. According to this protocol, treatment should be started with antimuscarinimedications. The only antimuscarinic medication for treating children with hyperactive bladder that is legal in Russia is oxybutinin (Driptane), that is presently considered to be the «golden standard» of pharmaceutical treatment of overactive bladder for patients of any age. This statement is based on the modern idea of overactive bladder pathogenesis, that presupposes detrusorhypersensibility to acetylcholine. However, in some cases it might be reasonable to use some other medications, physiotherapy, sometimes as part of complex therapy. If individual dosage is observed, which will enable preventing or significantly lowering possible side effects, oxybutinin will be still considered «the golden standard» for treating overactive bladder for years to come in cases when detrusor hypersensibility to acetylcholine is the key component of bladder dysfunction pathogenesis.Key words: overactive bladder, oxybutinin, urination disorder, children.